Synthesis of Cyclohexylcresols by Alkylation of Cresols with Cyclohexanol in the Presence of Perchloric Acid - Ashaduzzaman, Md.; Chowdhury, A. M. Sarwaruddin; Saha, Manoranjan (Dhaka University Journal of Science, 2012)
Cyclohexylcresols were synthesized in high yield by the alkylation of cresols with cyclohexanol in the presence of perchloric acid as catalyst. The effects of the variation of temperature, molar ratio of cresol to cyclohexanol, time of reaction and amount of catalyst on the reactions were also extensively studied. The products were confirmed by spectral means and physicochemical constants. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11503 Dhaka Univ. J. Sci. 60(2): 195-198, 2012 (July)